2004
DOI: 10.1186/1471-2164-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional signature of an adult brain tumor in Drosophila

Abstract: Background: Mutations and gene expression alterations in brain tumors have been extensively investigated, however the causes of brain tumorigenesis are largely unknown. Animal models are necessary to correlate altered transcriptional activity and tumor phenotype and to better understand how these alterations cause malignant growth. In order to gain insights into the in vivo transcriptional activity associated with a brain tumor, we carried out genome-wide microarray expression analyses of an adult brain tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 88 publications
(97 reference statements)
1
13
0
Order By: Relevance
“…Consistent with our hypothesis, mRNA levels of four genes expressed in Type I and Type II neural progenitors: asense ( ase ), deadpan ( dpn ), miranda ( mira ) and klumpfuss ( klu ), were all upregulated in heads from hemizygous brat chs /Df(2L)ED1272 flies, compared with heads from brat chs /+ controls ( Figure 6B ). These data are consistent with a previous study that found an increase in dpn , mira and klu mRNA in another brat mutant ( Loop et al 2004 ). We also found an increase in pointed P1 mRNA levels in brat chs /Df(2L)ED1272 flies ( Figure 6B ), which specifically implicates involvement of the Type II lineage.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with our hypothesis, mRNA levels of four genes expressed in Type I and Type II neural progenitors: asense ( ase ), deadpan ( dpn ), miranda ( mira ) and klumpfuss ( klu ), were all upregulated in heads from hemizygous brat chs /Df(2L)ED1272 flies, compared with heads from brat chs /+ controls ( Figure 6B ). These data are consistent with a previous study that found an increase in dpn , mira and klu mRNA in another brat mutant ( Loop et al 2004 ). We also found an increase in pointed P1 mRNA levels in brat chs /Df(2L)ED1272 flies ( Figure 6B ), which specifically implicates involvement of the Type II lineage.…”
Section: Resultssupporting
confidence: 94%
“…, brat k06028 , brat ts1 and brat fs1 ) ( Arama et al 2000 ). An adult brain overgrowth phenotype had been observed in homozygous brat k06028 mutants carrying a transposable element inserted into a non-coding region of the brat locus ( Loop et al 2004 ). However, we were unable to obtain viable adults even at low temperatures (18°) from any of the abovementioned lines and therefore couldn’t assess their neurodegenerative phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…We examined roles for brat during metamorphosis because, unlike the other six 20E primary-response genes described above, a brat mutant allele is available ( brat k06028 ) that allows an assessment of its functions during later stages of development [ 25 , 50 ]. The brat k06028 P -element maps to the fourth exon of the brat gene.…”
Section: Resultsmentioning
confidence: 99%
“…Genomewide microarray analysis of Drosophila brain tumor caused by the disfunction of the Brat tumor suppressor gene has identified over three hundred associated genes. Sixty of these sequences show homology to existing mammalian genes involved in tumor development [31]. As in human cancers, loss of heterozygosity can lead to tumor formation as reported in the case of the warts ( wts ) sequence.…”
Section: Senescence Cancer and Immunosuppressive Virusesmentioning
confidence: 99%